1994
DOI: 10.1111/j.1651-2227.1994.tb13433.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of growth hormone binding sites in rat brain

Abstract: The binding of 125I‐labelled rat growth hormone (GH) to different areas in the brain was studied in male Sprague‐Dawley rats. A high density of GH binding was found in the choroid plexus, hypothalamus, hippocampus, pituitary and spinal cord, whereas a lower binding density was observed in the cortex. Binding of the hormone to the various brain regions was age dependent. Binding was also dependent on time, pH and protein concentration. The binding affinity of the labelled hormone to choroid plexus was 4.3 per n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 20 publications
4
37
0
2
Order By: Relevance
“…However, prolactin binding is found mainly in the female rat brain (42). Therefore, we believe that the hormone-induced effect on the NMDA receptor subunits seen here represents effects mediated through pure GHR sites, which are abundant in male rat hippocampus (17).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, prolactin binding is found mainly in the female rat brain (42). Therefore, we believe that the hormone-induced effect on the NMDA receptor subunits seen here represents effects mediated through pure GHR sites, which are abundant in male rat hippocampus (17).…”
Section: Discussionmentioning
confidence: 87%
“…Studies have described a decreased density of GH-binding sites with aging in the male rat brain (17). In certain human brain tissues both the GHR protein, as assessed by receptor binding, and the GHR mRNA decrease by aging (15,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decline in GH binding as a function of age was observed in all areas except for the thalamus [21]. GH-binding sites have also been found in multiple regions of the rat brain by Zhai et al [22], who showed binding sites in the choroid plexus, hypothalamus, hippocampus, pituitary and spinal cord with a decrease in binding in an age dependent manner.…”
Section: Expression Of Ghr In the Brainmentioning
confidence: 82%
“…GH was not expressed at a detectable level in animals exposed to the delay paradigm. Although GH receptors exist in the hippocampus (Zhai et al, 1994), very little is known about the GH expression of itself outside the pituitary. It has been assumed that a source of GH lies outside the brain, or that the GH receptor in the brain has a ligand other than GH itself such as the GH-like substance which is sensitive to brain injury (reviewed in Scheepens et al, 2000).…”
Section: Donahue Et Almentioning
confidence: 99%